Method for preparing sustainable aviation kerosene through bio-based CO2 hydrogenation

By combining Fe/Mn-CaO, NiMoGa and metal oxide-molecular sieve catalysts, the problem of CO2 resource utilization in biogas was solved, and the efficient and stable conversion of biogas into aromatic-based aviation kerosene was achieved.

CN120888324APending Publication Date: 2025-11-04SHANGHAI HUA FENGHE BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202511072082.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing technologies have failed to effectively utilize CO2 resources in biogas, resulting in large emissions and waste of carbon resources. Furthermore, existing catalysts are not stable enough when biogas is converted into syngas.

Method used

Fe/Mn-CaO was used as the CO2 adsorption and separation agent, NiMoGa ternary liquid metal was used as the methane decarbonization and hydrogen production catalyst, and metal oxide-molecular sieve was used as the CO2 hydrogenation catalyst for the synthesis of aromatic aviation kerosene. The catalytic performance was improved by combining lanthanides and transition metals to form an ABO3 type perovskite structure and by adding structure directing agents.

Benefits of technology

This method achieves efficient resource utilization of CO2 in biogas, and synthesizes aromatic-based aviation kerosene with high conversion rate and high stability, thus solving the problem of biogas resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120888324A_ABST
    Figure CN120888324A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing sustainable aviation kerosene through CO2 hydrogenation in biogas. The method comprises the following steps: taking Fe / Mn-CaO as a CO2 adsorption separating agent, taking NiMoGa ternary liquid metal as a catalyst for methane decarbonization hydrogen production, and taking a metal oxide-molecular sieve as a catalyst for synthesizing aryl aviation kerosene through CO2 hydrogenation. According to the metal oxide-molecular sieve catalyst for synthesizing the aromatic sustainable aviation kerosene through CO2 hydrogenation, a metal oxide (ABO3) with a perovskite structure is synthesized through a sol-gel method, and the metal oxide (ABO3) is physically mixed with a molecular sieve; a in ABO3 is lanthanum, and a B element comprises iron, chromium, cobalt or nickel; the molecular sieve contains ZSM-5 (Zeolite Socony Mobil-5), ZSM-11 (Zeolite Socony According to the oxide catalyst disclosed by the invention, a polydentate chelate is formed by metal nitrate and citric acid, and a special perovskite structure can be formed through simple drying and roasting, so that the oxide catalyst has excellent carburization resistance, and a formed oxygen-containing intermediate is diffused into a zeolite molecular sieve to form aromatic aviation kerosene; the preparation of aryl aviation kerosene from bio-based CO2 hydrogenation is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention focuses on the field of biofuels, specifically relating to a method and catalyst for the synthesis of aromatic-based sustainable jet fuel from biogas CO2 hydrogenation. Background Technology

[0002] The decomposition of biomass or solid waste such as wet garbage generates a large amount of biogas, mainly composed of 20-40% CO2, 50-80% CH4, and small amounts of H2 and N2. Currently, biogas is widely used for combustion or power generation. However, due to its low energy density and the fact that all the CO2 produced during combustion and that it contains is emitted into the atmosphere, it causes environmental pollution and wastes carbon resources. Therefore, how to comprehensively utilize biogas as a resource is an urgent problem to be solved. Aviation kerosene is currently the main fuel in the aviation industry, and its supply heavily relies on traditional petrochemical processes such as crude oil distillation and naphtha reforming. Using biogas as a raw material, through CO2 adsorption and separation, methane decarbonization to H2, and utilizing a Fischer-Tropsch-like synthesis (CO2+H2) to produce multi-carbon aromatics and long-chain alkanes via a non-petroleum route, a new route for the resource utilization of biogas is provided.

[0003] Chinese patent (CN202410886401.5) discloses a biogas hydrogen production catalyst, its preparation method, and its application. Using a Ni / ZrO2-Al2O3 catalyst to produce hydrogen from biogas improves methane conversion and hydrogen production rates, but other components in the biogas are not utilized, resulting in significant CO2 emissions. Chinese patent (CN117019162B) discloses a Ni-CeAlO3 / hydrotalcite catalyst for the complete conversion of biogas components into a suitable alcohol mixture, its preparation method, and its application. Although the catalyst exhibits high CH4 and CO2 conversion rates and converts biogas into syngas, the final product is syngas, and its stability needs improvement. In summary, there is an urgent need to develop a process and method for the comprehensive resource utilization of biogas for the production of high-value chemicals.

[0004] This invention addresses the problem of resource utilization of CO2 in biogas by providing a method for the atom-economical conversion of biogas into aromatic-based aviation kerosene. CO2 in biogas is captured and separated from methane, followed by methane decarbonization to produce hydrogen. The captured CO2 and H2 obtained from methane decarbonization are mixed in a certain proportion, and the molar ratio of H2 / CO2 in the mixture can be adjusted to achieve the synthesis of aromatic-based aviation kerosene from biogas. Summary of the Invention

[0005] This invention addresses the problem of biogas resource utilization by providing a catalyst for the synthesis of aromatic-based aviation kerosene from biogas and its efficient preparation method. The method involves capturing CO2 from biogas and separating it from methane, followed by methane decarbonization to produce hydrogen. The captured CO2 and the H2 obtained from methane decarbonization are then mixed in a specific ratio to achieve the synthesis of aromatic-based aviation kerosene from biogas. This catalyst for synthesizing aromatic-based aviation kerosene features a simple synthesis method, high activity, and high selectivity.

[0006] The technical solution adopted in this application is: a method for synthesizing aromatic-based aviation kerosene from biogas, characterized by: using Fe / Mn-CaO as a CO2 adsorption and separation agent, NiMoGa ternary liquid metal as a methane decarbonization and hydrogen production catalyst, and metal oxide-molecular sieve as a catalyst for CO2 hydrogenation to synthesize aromatic-based aviation kerosene. The method mainly utilizes the following two methods to jointly promote and improve the catalytic performance of synthesizing aromatic-based aviation kerosene from biogas derivatives;

[0007] Firstly, lanthanides are selected in combination with transition metals such as iron, chromium, cobalt, or nickel to form metal oxides with an ABO3-type perovskite structure. The transition metals are embedded in the perovskite lattice, thereby avoiding reduction and phase transition in the reaction and improving the catalytic performance of the catalyst.

[0008] Secondly, the addition of different structure-directing agents: tetrapropylammonium hydroxide (TPAOH) or tetrabutylammonium hydroxide (TBAOH) can control the topology of molecular sieves, forming molecular sieves with single or symbiotic topologies, thereby improving the pore structure of molecular sieves.

[0009] The method for synthesizing aromatic-based aviation kerosene from biogas includes the following steps:

[0010] 1. Using Fe / Mn-CaO as the CO2 adsorption and separation agent, CO2 and CH4 are separated;

[0011] 2. Using NiMoGa ternary liquid metal as a catalyst for CH4 decarbonization and hydrogen production, for the production of H2;

[0012] 3. Using metal oxide-molecular sieves as CO2 hydrogenation catalysts to produce aromatic-based aviation kerosene;

[0013] 4. The metal oxide-molecular sieve catalyst involved in process 3, characterized in that,

[0014] (1) The metal oxide is prepared by the sol-gel method, including but not limited to iron nitrate, lanthanum nitrate, chromium nitrate, cobalt nitrate or nickel nitrate as metal salts dissolved in citric acid and ethylene glycol in deionized water, forming a uniform solution through the complexation between the metal and citric acid, and then drying to obtain the metal oxide precursor; the catalyst precursor is obtained by calcination in a muffle furnace.

[0015] (2) The molecular sieves include, but are not limited to, ZSM-5, ZSM-11, or a symbiotic ZSM-5-ZSM-11. They are prepared using a certain proportion of Si / Al raw materials and a structure-directing agent through hydrothermal treatment, ion exchange, and high-temperature calcination.

[0016] (3) The metal oxide-molecular sieve catalyst is formed by physical mixing.

[0017] In step (1), the added metal nitrate is two or more of the following: ferric nitrate, lanthanum nitrate, chromium nitrate, zinc nitrate, zirconium nitrate, or sodium nitrate, with a molar composition of LaM x N 1-x O3, x is 0-1, and the amount of citric acid added is: citric acid:metal cation (molar ratio) = 1-2.5. The complexation temperature is 80℃, the drying temperature is 120℃, and the calcination temperature is 500℃ for 5 hours.

[0018] In step (2), tetraethyl orthosilicate (TEOS) was used as the silicon source, and aluminum nitrate nonahydrate was used as the aluminum source. Tetraethylammonium hydroxide (TEAOH) or tetrapropylammonium hydroxide (TPAOH) was used as the structure directing agent; the hydrothermal reaction temperature was 140℃~180℃, and the reaction time was 48h-120h. Ion exchange was performed in a 1M ammonium chloride solution at 80℃ for 2h, with a solid-liquid ratio of 30, repeated three times. The muffle furnace calcination temperature was 550℃, and the time was 5h.

[0019] In step (3), the preparation of the metal oxide-molecular sieve catalyst is characterized by uniformly mixing the metal oxide and molecular sieve by physical mixing in a certain proportion.

[0020] The above-mentioned technical solution adopted in this application can achieve the following beneficial effects:

[0021] This application uses biogas as raw material, and after CO2 adsorption and separation in a fixed-bed reactor, the separated CH4 is decarbonized and hydrogen produced in the fixed-bed reactor. Subsequently, the derived gas (CO2+H2) is synthesized into aromatic aviation kerosene in the fixed-bed reactor. The LaFe of the synthesized aromatic aviation kerosene is obtained after modification of the derived gas (CO2+H2). x Cr 1-x O3 / ZSM-5-ZSM-11 and catalyst exhibit high CO2 conversion rate (%), aromatic aviation kerosene (C8-C) 16 It has high stability for 500 hours. Attached Figure Description

[0022] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings:

[0023] Figure 1 Roadmap for the synthesis of sustainable aromatic-based jet fuel from bio-based CO2 hydrogenation Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0025] Example 1

[0026] (1) Preparation of Fe / Mn-CaO catalyst

[0027] Dissolve 6.37 g of calcium nitrate tetrahydrate, 0.60 g of manganese nitrate tetrahydrate, and 0.16 g of ferric nitrate nonahydrate in 60 mL of deionized water until fully dissolved. Add 0.98 g of hexadecyltrimethylammonium bromide (CTAB) to the solution. After thorough mixing, add 11.33 g of citric acid monohydrate to the solution. Stir in an oil bath at 70 °C for 3 h, then adjust the pH to approximately 9 with ammonia. Continue stirring in a water bath at 70 °C until a gel forms. Dry the resulting gel in an oven at 120 °C for 12 h and calcine it in a muffle furnace at 900 °C for 4 h.

[0028] (2) Preparation of NiMoGa catalyst

[0029] NiO and MoO3 powders were mixed with metallic Ga at a molar ratio of Mo:Ni:Ga = 1:2.8:98.5 and placed in a quartz tube. The mixture was purged with inert gas for 1 hour, then heated to 700°C. 20 mL / min of 75% H2 / N2 was then introduced and the mixture was held at 700°C for 1 hour, slowly reducing it to a NiMo-Bi liquid alloy catalyst. Subsequently, the mixture was purged with inert gas to obtain the liquid metal alloy catalyst.

[0030] (3) Preparation of LaFeO3 / H-ZSM-5 catalyst

[0031] Step 1: Synthesis of the metal oxide. 5.35 g of lanthanum nitrate hexahydrate, 5.22 g of ferric nitrate nonahydrate, 6.39 g of citric acid, and 0.38 g of ethylene glycol were dissolved in deionized water and stirred vigorously for 1 h. The mixture was heated to 80 °C and stirred continuously until a gel formed. It was then dried in air at 120 °C for 12 h. The resulting catalyst precursor was calcined in a muffle furnace at 500 °C for 5 h.

[0032] Step 2: Synthesis of H-ZSM-5. 11.2 g tetraethyl orthosilicate, 13.1 g tetrapropylammonium hydroxide, 0.52 g aluminum nitrate nonahydrate, 0.1 g sodium hydroxide, 0.1 g isopropanol, and 2 g urea were dissolved in deionized water and stirred vigorously for 6 h. The mixture was then transferred to a high-pressure hydrothermal reactor, and the reaction temperature was set to 180 °C for 48 h. After cooling to room temperature, the product was washed several times with distilled water and calcined in air in a muffle furnace (550 °C, 5 h). The obtained powder sample was weighed, and each 1 g of molecular sieve was subjected to ion exchange with 30 mL of 1 M NH4Cl solution at 80 °C for 2 h each time, for three cycles. Na-ZSM-5 was converted to NH4-ZSM-5 via cation exchange. The resulting powder was calcined in a muffle furnace at 550 °C for 5 h.

[0033] Step 3: Physically mix H-ZSM-5 and LaFeO3 in a 1:1 mass ratio. After the resulting mixture is compressed into tablets, it is crushed and screened to obtain 40-50 mesh particles.

[0034] (4) Catalyst performance testing

[0035] CO2 adsorption and separation from biogas was carried out in a dual-channel fixed-bed reactor. 1.0g of Fe / Mn-CaO catalyst was mixed with 0.5g of 40-60 mesh quartz sand and loaded into the reactor. After treatment at 750℃ under N2 atmosphere for 1h, the reactor was switched to biogas for CO2 adsorption and separation.

[0036] The decarbonization of methane to produce hydrogen was carried out in a fixed-bed reactor. 2.0 g of NiO and MoO3 powder were mixed with metallic Ga and packed into a quartz tube (8 mm inner diameter). The tube was purged with inert gas for 1 h, heated to 700 °C, and then purged with 20 mL / min of 75% H2 / N2. The mixture was held at 700 °C for 1 h to slowly reduce the catalyst to a NiMo-Bi liquid alloy, at which point the gas was switched to CH4 for the reaction.

[0037] The synthesis of aromatic-based aviation kerosene from biogas derivatives was carried out in a fixed-bed reactor. 2.0 g of LaFeO3 / H-ZSM-5 catalyst was charged into the fixed-bed reactor, and the reaction tube was heated to a set temperature of 350 °C. The reactor was treated with H2 at a flow rate of 50 mL / min for 2 h. After treatment, the biogas derivatives (H2:CO2 = 3:1) were switched to the reactor, and the reaction was carried out at a pressure of 3.0 MPa and a space velocity of 500 mL·g⁻¹. 1 ·h- 1 Catalyst CO2 conversion rate, aromatics selectivity (C8-C4) 16 The results of the stability evaluation are shown in the table below:

[0038]

[0039]

[0040] Example 2

[0041] (1) Preparation of Fe / Mn-CaO catalyst

[0042] Dissolve 6.37 g of calcium nitrate tetrahydrate, 0.60 g of manganese nitrate tetrahydrate, and 0.16 g of ferric nitrate nonahydrate in 60 mL of deionized water until fully dissolved. Add 0.98 g of hexadecyltrimethylammonium bromide (CTAB) to the solution. After thorough mixing, add 11.33 g of citric acid monohydrate to the solution. Stir in an oil bath at 70 °C for 3 h, then adjust the pH to approximately 9 with ammonia. Continue stirring in a water bath at 70 °C until a gel forms. Dry the resulting gel in an oven at 120 °C for 12 h and calcine it in a muffle furnace at 900 °C for 4 h.

[0043] (2) Preparation of NiMoGa catalyst

[0044] NiO and MoO3 powders were mixed with metallic Ga at a molar ratio of Mo:Ni:Ga = 1:2.8:98.5 and placed in a quartz tube. The mixture was purged with inert gas for 1 hour, then heated to 700°C. 20 mL / min of 75% H2 / N2 was then introduced and the mixture was held at 700°C for 1 hour, slowly reducing it to a NiMo-Bi liquid alloy catalyst. Subsequently, the mixture was purged with inert gas to obtain the liquid metal alloy catalyst.

[0045] (3) Preparation of LaCoO3 / H-ZSM-5 catalyst

[0046] Step 1: Synthesis of the metal oxide. 5.35 g of lanthanum nitrate hexahydrate, 3.76 g of cobalt nitrate hexahydrate, 6.39 g of citric acid, and 0.38 g of ethylene glycol were dissolved in deionized water and stirred vigorously for 1 h. The mixture was heated to 80 °C and stirred continuously until a gel formed. It was then dried in air at 120 °C for 12 h. The resulting catalyst precursor was calcined in a muffle furnace at 500 °C for 5 h.

[0047] Step 2: Synthesis of H-ZSM-5. 11.2 g tetraethyl orthosilicate, 13.1 g tetrapropylammonium hydroxide, 0.52 g aluminum nitrate nonahydrate, 0.1 g sodium hydroxide, 0.1 g isopropanol, and 2 g urea were dissolved in deionized water and stirred vigorously for 6 h. The mixture was then transferred to a high-pressure hydrothermal reactor, and the reaction temperature was set to 180 °C for 48 h. After cooling to room temperature, the product was washed several times with distilled water and calcined in air in a muffle furnace (550 °C, 5 h). The obtained powder sample was weighed, and each 1 g of molecular sieve was subjected to ion exchange with 30 mL of 1 M NH4Cl solution at 80 °C for 2 h each time, for three cycles. Na-ZSM-5 was converted to NH4-ZSM-5 via cation exchange. The resulting powder was calcined in a muffle furnace at 550 °C for 5 h.

[0048] Step 3: Physically mix H-ZSM-5 and LaCoO3 in a 1:1 mass ratio. After the resulting mixture is compressed into tablets, it is crushed and screened to obtain 40-50 mesh particles.

[0049] (4) Catalyst performance testing

[0050] CO2 adsorption and separation from biogas was carried out in a dual-channel fixed-bed reactor. 1.0g of Fe / Mn-CaO catalyst was mixed with 0.5g of 40-60 mesh quartz sand and loaded into the reactor. After treatment at 750℃ under N2 atmosphere for 1h, the reactor was switched to biogas for CO2 adsorption and separation.

[0051] The decarbonization of methane to produce hydrogen was carried out in a fixed-bed reactor. 2.0 g of NiO and MoO3 powder were mixed with metallic Ga and packed into a quartz tube (8 mm inner diameter). The tube was purged with inert gas for 1 h, heated to 700 °C, and then purged with 20 mL / min of 75% H2 / N2. The mixture was held at 700 °C for 1 h to slowly reduce the catalyst to a NiMo-Bi liquid alloy, at which point the gas was switched to CH4 for the reaction.

[0052] The synthesis of aromatic-based aviation kerosene from biogas derivatives was carried out in a fixed-bed reactor. 2.0 g of LaCoO3 / H-ZSM-5 catalyst was charged into the fixed-bed reactor, and the reaction tube was heated to a set temperature of 350 °C. The reactor was treated with H2 at a flow rate of 50 mL / min for 2 h. After treatment, the reactor was switched to biogas derivatives (H2:CO2 = 3:1) at a pressure of 3.0 MPa and a space velocity of 500 mL·g⁻¹. -1 ·h -1 Catalyst CO2 conversion rate, aromatic liquid-phase selectivity (C8-C5) 16 The results of the stability evaluation are shown in the table below:

[0053]

[0054] Example 3

[0055] (1) Preparation of Fe / Mn-CaO catalyst

[0056] Dissolve 6.37 g of calcium nitrate tetrahydrate, 0.60 g of manganese nitrate tetrahydrate, and 0.16 g of ferric nitrate nonahydrate in 60 mL of deionized water until fully dissolved. Add 0.98 g of hexadecyltrimethylammonium bromide (CTAB) to the solution. After thorough mixing, add 11.33 g of citric acid monohydrate to the solution. Stir in an oil bath at 70 °C for 3 h, then adjust the pH to approximately 9 with ammonia. Continue stirring in a water bath at 70 °C until a gel forms. Dry the resulting gel in an oven at 120 °C for 12 h and calcine it in a muffle furnace at 900 °C for 4 h.

[0057] (2) Preparation of NiMoGa catalyst

[0058] NiO and MoO3 powders were mixed with metallic Ga at a molar ratio of Mo:Ni:Ga = 1:2.8:98.5 and placed in a quartz tube. The mixture was purged with inert gas for 1 hour, then heated to 700°C. 20 mL / min of 75% H2 / N2 was then introduced and the mixture was held at 700°C for 1 hour, slowly reducing it to a NiMo-Bi liquid alloy catalyst. Subsequently, the mixture was purged with inert gas to obtain the liquid metal alloy catalyst.

[0059] (3) Preparation of LaFeO3 / ZSM-5-ZSM-11 catalyst

[0060] Step 1: Synthesis of the metal oxide. 5.35 g of lanthanum nitrate hexahydrate, 5.22 g of ferric nitrate nonahydrate, 6.39 g of citric acid, and 0.38 g of ethylene glycol were dissolved in deionized water and stirred vigorously for 1 h. The mixture was heated to 80 °C and stirred continuously until a gel formed. It was then dried in air at 120 °C for 12 h. The resulting catalyst precursor was calcined in a muffle furnace at 500 °C for 5 h.

[0061] Step 2: Synthesis of ZSM-5-ZSM-11. Dissolve 0.1g sodium hydroxide, 0.17g sodium aluminate, 10.8g tetraethyl orthosilicate, and 9.3g tetrabutylammonium hydroxide in deionized water and stir for 3 hours to obtain a suspension. Let stand at room temperature for 2 hours, then place in a hydrothermal reactor and set the reaction temperature to 170℃ and the reaction time to 72 hours. Cool to room temperature, wash the product several times with distilled water, and calcine in air in a muffle furnace (550℃, 5 hours). Weigh the obtained powder sample, and perform ion exchange with 1M NH4Cl solution (30mL) at 80℃ for 2 hours each time, three times. Calcine the obtained powder in a muffle furnace at 550℃ for 5 hours.

[0062] Step 3: Physically mix ZSM-5-ZSM-11 and LaFeO3 in a 1:1 mass ratio. After the resulting mixture is compressed into tablets, it is crushed and screened to obtain 40-50 mesh particles.

[0063] (4) Catalyst performance testing

[0064] CO2 adsorption and separation from biogas was carried out in a dual-channel fixed-bed reactor. 1.0g of Fe / Mn-CaO catalyst was mixed with 0.5g of 40-60 mesh quartz sand and loaded into the reactor. After treatment at 750℃ under N2 atmosphere for 1h, the reactor was switched to biogas for CO2 adsorption and separation.

[0065] The decarbonization of methane to produce hydrogen was carried out in a fixed-bed reactor. 2.0 g of NiO and MoO3 powder were mixed with metallic Ga and packed into a quartz tube (8 mm inner diameter). The tube was purged with inert gas for 1 h, heated to 700 °C, and then purged with 20 mL / min of 75% H2 / N2. The mixture was held at 700 °C for 1 h to slowly reduce the catalyst to a NiMo-Bi liquid alloy, at which point the gas was switched to CH4 for the reaction.

[0066] The synthesis of aromatic-based aviation kerosene from biogas derivatives was carried out in a fixed-bed reactor. 2.0 g of LaFeO3 / ZSM-5-ZSM-11 catalyst was charged into the fixed-bed reactor, and the reaction tube was heated to a set temperature of 350 °C. The reactor was treated with H2 at a flow rate of 50 mL / min for 2 h. After treatment, the reaction was switched to biogas derivatives (H2:CO2 = 3:1) at a pressure of 3.0 MPa and a space velocity of 500 mL·g⁻¹. -1 ·h -1 Catalyst CO2 conversion rate, aromatic liquid-phase selectivity (C8-C5) 16 The results of the stability evaluation are shown in the table below:

[0067]

[0068] Example 4

[0069] (1) Preparation of Fe / Mn-CaO catalyst

[0070] Dissolve 6.37 g of calcium nitrate tetrahydrate, 0.60 g of manganese nitrate tetrahydrate, and 0.16 g of ferric nitrate nonahydrate in 60 mL of deionized water until fully dissolved. Add 0.98 g of hexadecyltrimethylammonium bromide (CTAB) to the solution. After thorough mixing, add 11.33 g of citric acid monohydrate to the solution. Stir in an oil bath at 70 °C for 3 h, then adjust the pH to approximately 9 with ammonia. Continue stirring in a water bath at 70 °C until a gel forms. Dry the resulting gel in an oven at 120 °C for 12 h and calcine it in a muffle furnace at 900 °C for 4 h.

[0071] (2) Preparation of NiMoGa catalyst

[0072] NiO and MoO3 powders were mixed with metallic Ga at a molar ratio of Mo:Ni:Ga = 1:2.8:98.5 and placed in a quartz tube. The mixture was purged with inert gas for 1 hour, then heated to 700°C. 20 mL / min of 75% H2 / N2 was then introduced and the mixture was held at 700°C for 1 hour, slowly reducing it to a NiMo-Bi liquid alloy catalyst. Subsequently, the mixture was purged with inert gas to obtain the liquid metal alloy catalyst.

[0073] (3) Preparation of LaCrO3 / H-ZSM-11 catalyst

[0074] Step 1: Synthesis of the metal oxide. 5.35 g of lanthanum nitrate hexahydrate, 3.05 g of cadmium nitrate, 6.39 g of citric acid, and 0.38 g of ethylene glycol were dissolved in deionized water and stirred vigorously for 1 h. The mixture was heated to 80 °C and stirred continuously until a gel formed. It was then dried in air at 120 °C for 12 h. The resulting catalyst precursor was calcined in a muffle furnace at 500 °C for 5 h and named LaFeO3.

[0075] Step 2: Synthesis of H-ZSM-5. Dissolve 0.1g sodium hydroxide, 0.17g sodium aluminate, 10.8g tetraethyl orthosilicate, and 9.3g tetrabutylammonium hydroxide in deionized water and stir for 3 hours to obtain a suspension. Let stand at room temperature for 2 hours, then place in a hydrothermal reactor and set the reaction temperature to 130℃ and the reaction time to 120 hours. Cool to room temperature, wash the product several times with distilled water, and calcine in air in a muffle furnace (550℃, 5 hours). Weigh the obtained powder sample, and perform ion exchange with 1M NH4Cl solution (30mL) at 80℃ for 2 hours each time, three times. Convert Na-ZSM-11 to NH4-ZSM-11 via cation exchange. Calcine the obtained powder in a muffle furnace at 550℃ for 5 hours.

[0076] Step 3: Physically mix H-ZSM-11 and LaCrO3 in a 1:1 mass ratio. After the resulting mixture is compressed into tablets, it is crushed and screened to obtain 40-50 mesh particles.

[0077] (4) Catalyst performance testing

[0078] CO2 adsorption and separation from biogas was carried out in a dual-channel fixed-bed reactor. 1.0g of Fe / Mn-CaO catalyst was mixed with 0.5g of 40-60 mesh quartz sand and loaded into the reactor. After treatment at 750℃ under N2 atmosphere for 1h, the reactor was switched to biogas for CO2 adsorption and separation.

[0079] The decarbonization of methane to produce hydrogen was carried out in a fixed-bed reactor. 2.0 g of NiO and MoO3 powder were mixed with metallic Ga and packed into a quartz tube (8 mm inner diameter). The tube was purged with inert gas for 1 h, heated to 700 °C, and then purged with 20 mL / min of 75% H2 / N2. The mixture was held at 700 °C for 1 h to slowly reduce the catalyst to a NiMo-Bi liquid alloy, at which point the gas was switched to CH4 for the reaction.

[0080] The synthesis of aromatic-based aviation kerosene from biogas derivatives was carried out in a fixed-bed reactor. 2.0 g of LaCrO3 / H-ZSM-11 catalyst was charged into the fixed-bed reactor, and the reaction tube was heated to a set temperature of 350 °C. The reactor was treated with H2 at a flow rate of 50 mL / min for 2 h. After treatment, the reaction was switched to biogas derivatives (H2:CO2 = 3:1) at a pressure of 3.0 MPa and a space velocity of 500 mL·g⁻¹. -1 ·h -1 Catalyst CO2 conversion rate, aromatic liquid-phase selectivity (C8-C5) 16 The results of the stability evaluation are shown in the table below:

[0081]

[0082] Example 5

[0083] (1) Preparation of Fe / Mn-CaO catalyst

[0084] Dissolve 6.37 g of calcium nitrate tetrahydrate, 0.60 g of manganese nitrate tetrahydrate, and 0.16 g of ferric nitrate nonahydrate in 60 mL of deionized water until fully dissolved. Add 0.98 g of hexadecyltrimethylammonium bromide (CTAB) to the solution. After thorough mixing, add 11.33 g of citric acid monohydrate to the solution. Stir in an oil bath at 70 °C for 3 h, then adjust the pH to approximately 9 with ammonia. Continue stirring in a water bath at 70 °C until a gel forms. Dry the resulting gel in an oven at 120 °C for 12 h and calcine it in a muffle furnace at 900 °C for 4 h.

[0085] (2) Preparation of NiMoGa catalyst

[0086] NiO and MoO3 powders were mixed with metallic Ga at a molar ratio of Mo:Ni:Ga = 1:2.8:98.5 and placed in a quartz tube. The mixture was purged with inert gas for 1 hour, then heated to 700°C. 20 mL / min of 75% H2 / N2 was then introduced and the mixture was held at 700°C for 1 hour, slowly reducing it to a NiMo-Bi liquid alloy catalyst. Subsequently, the mixture was purged with inert gas to obtain the liquid metal alloy catalyst.

[0087] (3)LaFe 0.8 Cr 0.2 Preparation of O3 / ZSM-5-ZSM-11 catalyst

[0088] Step 1: Synthesis of metal oxides. 5.35 g lanthanum nitrate hexahydrate, 4.18 g ferric nitrate nonahydrate, 0.61 g cadmium nitrate, 6.39 g citric acid, and 0.38 g ethylene glycol were dissolved in deionized water and stirred vigorously for 1 h. The mixture was heated to 80 °C and stirred continuously until a gel formed. It was then dried in air at 120 °C for 12 h. The resulting catalyst precursor was calcined in a muffle furnace at 500 °C for 5 h.

[0089] Step 2: Synthesis of ZSM-5-ZSM-11. Dissolve 0.1g sodium hydroxide, 0.17g sodium aluminate, 10.8g tetraethyl orthosilicate, and 9.3g tetrabutylammonium hydroxide in deionized water and stir for 3 hours to obtain a suspension. Let stand at room temperature for 2 hours, then place in a hydrothermal reactor and set the reaction temperature to 170℃ and the reaction time to 72 hours. Cool to room temperature, wash the product several times with distilled water, and calcine in air in a muffle furnace (550℃, 5 hours). Weigh the obtained powder sample, and perform ion exchange with 1g of molecular sieve using 30mL of 1M NH4Cl solution at 80℃ for 2 hours each time, repeating three times. Calcine the obtained powder in a muffle furnace at 550℃ for 5 hours.

[0090] Step 3: Physically mix ZSM-5-ZSM-11 and LaFe in a 1:1 mass ratio. 0.8 Cr 0.2 O3, the resulting mixture powder is compressed into tablets, then crushed and screened to obtain 40-50 mesh particles.

[0091] (4) Catalyst performance testing

[0092] CO2 adsorption and separation from biogas was carried out in a dual-channel fixed-bed reactor. 1.0g of Fe / Mn-CaO catalyst was mixed with 0.5g of 40-60 mesh quartz sand and loaded into the reactor. After treatment at 750℃ under N2 atmosphere for 1h, the reactor was switched to biogas for CO2 adsorption and separation.

[0093] The decarbonization of methane to produce hydrogen was carried out in a fixed-bed reactor. 2.0 g of NiO and MoO3 powder were mixed with metallic Ga and packed into a quartz tube (8 mm inner diameter). The tube was purged with inert gas for 1 h, heated to 700 °C, and then purged with 20 mL / min of 75% H2 / N2. The mixture was held at 700 °C for 1 h to slowly reduce the catalyst to a NiMo-Bi liquid alloy, at which point the gas was switched to CH4 for the reaction.

[0094] The synthesis of aromatic-based aviation kerosene from biogas derivatives was carried out in a fixed-bed reactor. 2.0 g of LaFe... 0.8 Cr 0.2 The O3 / ZSM-5-ZSM-11 catalyst was loaded into a fixed-bed reactor, and the reaction tube was heated to a set temperature of 350℃. Reduction was carried out at a rate of 50 mL / min for 2 hours. After reduction, the reaction was switched to biogas derivative gas (H2:CO2 = 3:1) at a pressure of 3.0 MPa and a space velocity of 500 mL·g⁻¹. -1 ·h -1 Catalyst CO2 conversion rate, aromatic liquid-phase selectivity (C8-C5) 16 The results of the stability evaluation are shown in the table below:

[0095]

[0096] The above-described embodiments are merely illustrative of the technology and features of the present invention, and are intended to help those skilled in the art understand the content of the present invention and implement it accordingly. The scope of this patent should not be limited to these embodiments alone. All equivalent changes or modifications made in accordance with the spirit disclosed in this invention still fall within the scope of this patent.

Claims

1. A method for the hydrogenation of CO2 from biogas to synthesize sustainable aromatic-based aviation kerosene, characterized in that, The CO2 adsorption and separation in biogas is carried out in a fixed-bed reactor, characterized by an optimal adsorption-desorption temperature of 700-750℃ and an optimal adsorption-desorption interval of 30-50 min; the decarbonization of the separated CH4 to produce hydrogen is carried out in a fixed-bed reactor, with an optimal hydrogen production temperature of 600-800℃; the synthesis of aromatic aviation kerosene from the derivative gas (CO2+H2) is carried out in a fixed-bed reactor, with a metal oxide-molecular sieve catalyst loaded into the reactor, and the adsorbed and separated CO2 and H2 obtained from the decarbonization of methane (molar ratio 1:3) are introduced, the reaction temperature is 350℃, the reaction pressure is 3.0 MPa, and the reaction space velocity is 500 mL g. cat -1 h -1 .

2. A catalyst for the synthesis of sustainable aromatic-based aviation kerosene from CO2 hydrogenation in biogas, characterized in that: Fe / Mn-CaO is used as the CO2 adsorption and separation agent, NiMoGa ternary liquid metal is used as the methane decarbonization and hydrogen production catalyst, and metal oxide-molecular sieve is used as the catalyst for the synthesis of aromatic-based aviation kerosene from CO2 hydrogenation. (1) The A element in the metal oxide (ABO3) is lanthanum, and the B element includes, but is not limited to, iron, cerium, chromium, cobalt or nickel; (2) The molecular sieves include, but are not limited to, ZSM-5, ZSM-11 or symbiotic ZSM-5-ZSM-11; (3) The metal oxide-molecular sieve bifunctional catalyst is formed by physical mixing.

3. A method for synthesizing aviation kerosene-grade aromatics (C8-C4) by CO2 hydrogenation according to claim 2. 16 A method for preparing metal oxides, characterized in that, The sol-gel method is employed, and its steps are as follows: Step 1: Dissolve the metal nitrate in deionized water to obtain solution A; Step 2: Add citric acid and ethylene glycol to solution A, wherein the molar amount of citric acid added is 100-200% of the metal ions, and the molar amount of ethylene glycol added is 10-30% of the metal ions, and stir thoroughly to obtain mixed solution B; Step 3: Stir the mixed solution B in an oil bath at 80°C until a gel is formed. Then, dry the gel in an oven at 120°C for 24 hours and calcine it in a muffle furnace at 500°C for 5 hours to finally obtain the metal oxide.

4. A syngas-to-aromatic aviation kerosene (C8-C4) according to claim 2. 16 The method for preparing molecular sieves is characterized by, The steps are as follows: Step 1: Dissolve aluminum nitrate nonahydrate and sodium hydroxide in deionized water, then add a structure directing agent, which is tetrapropylammonium hydroxide (TPAOH) or tetrabutylammonium hydroxide (TBAOH). After stirring evenly, add tetraethyl orthosilicate (TEOS) to obtain solution A. Step 2: Place the solution A into a hydrothermal reactor lined with polytetrafluoroethylene. The hydrothermal reaction temperature is 140℃~180℃, the reaction time is 48h-120h, and the solution is calcined in a muffle furnace at 550℃ for 5h to obtain powder A. Step 3: Disperse the powder A in a 1M ammonium chloride solution, stir at 80°C for 2 hours, repeat three times, and calcine in a muffle furnace at 550°C for 5 hours to obtain the molecular sieve.

5. The method for preparing the metal oxide-molecular sieve catalyst according to claim 2, characterized in that, The metal oxides and molecular sieves obtained according to claims 2-3 are uniformly mixed using a physical mixing method in a certain proportion.

Citation Information

Patent Citations

  • Ni-CeAlO3 / hydrotalcite catalyst for converting all components of biogas into suitable alcohol mixed gas, preparation method and application thereof

    CN117019162B

  • Biogas hydrogen production catalyst as well as preparation method and application thereof

    CN118719037A

Cited By

  • Preparation method of sustainable aviation fuel

    CN121551053A